Comparison study between encapsulation of Acalypha indica Linn extracts with Chitosan-PCL and Chitosan-OA - Johari, Maizatul Akmal; Azmi, Azlin Suhaida; Jamaluddin, Jamarosliza; Hasham, Rosnani; Chee, Chin Fei; Ali, Fathilah (IOP Publishing Ltd, 2021)
Drug delivery is one of the major applications in the biodegradable polymer science. Chitosan is a non-toxic and naturally biodegradable polymer. It is soluble in acidic aqueous media and insoluble in higher pH media. Chitosan has been modified to improve its properties such as stability and the modified derivatives have been widely used in many applications especially for drug delivery. There are several kinds of chitosan modification. This study investigated the modification of chitosan with polyester-types of polymer and the fatty acidbased polymer. The aim of this study is to compare the formation encapsulation of chitosan-oleic acid conjugate (Ch-OA) and chitosan- polycaprolactone (PCL) copolymer for the encapsulation of Acalypha indica active compounds for drug delivery by using emulsion-solvent evaporation technique. The crude extracts have been extracted and the phytochemicals inside the crude extracts are less stable in nature. These active compounds need to be encapsulated to stabilize them and delivered well into the body system. As for conclusion, chitosan:PCL is able to form better encapsulation using this method.